HIGH-PERFORMANCE EMBEDDING IN DUAL IMAGES BASED ON PIXEL VALUE ORDERING METHOD - Cao Thị Luyen; Pham Minh Thai (Tạp chí Khoa học)
Reversible data hiding (RDH) not only protects information but also extends its applications across various fields. This paper improves the Pixel Value Ordering (PVO) algorithm to enhance embedding capacity in dual images. We developed an optimized embedding method, allowing for higher data embedding performance compared to related works. Experimental results demonstrate that, relative to similar methods, this improvement enhances both embedding capacity and image quality.